Mechanisms of development stimulation of the depressed territories of Ukraine: institutional aspects - Барановський, Микола (Human Geography Journal, 2016)
The existing normative legal base of Ukraine which regulates the mechanisms of defining the depressed areas of different types and measures for  their activation is analyzed;  the world experience of problem territories support is briefly characterized; the factors that prevent from making efficient mechanisms of development stimulation of problem regions in Ukraine are determined; the level of financing the sanitation actions of the depressed areas are defined; the gist of new approaches to the problem of activating the development of depressed territories of different types is divulged;  the essence, sources and volumes of financing, the priority targets and tasks of the existing regional development agreements concluded between some territories and the Cabinet of Ukraine are analyzed; the possible ways of mechanisms improvement of stimulation of Ukrainian depressed areas development are described.